The colposcopic atlas of schistosomiasis in the lower female genital tract based on studies in Malawi, Zimbabwe, Madagascar and South Africa. - Hanne M Norseth; Patricia D Ndhlovu; Elisabeth Kleppa; Bodo S Randrianasolo; Peter M Jourdan; Borghild Roald; Sigve D Holmen; Svein G Gundersen; Jayanthilall Bagratee; Mathias Onsrud; Eyrun F Kjetland (Public Library of Science (PLoS), 2014)
Schistosoma (S.) haematobium is a neglected tropical disease which may affect any part of the genital tract in women. Female genital schistosomiasis (FGS) may cause abnormal vaginal discharge, contact bleeding, genital tumours, ectopic pregnancies and increased susceptibility to HIV. Symptoms may mimic those typical of sexually transmitted infections (STIs) and women with genital schistosomiasis may be incorrectly diagnosed. An expert consensus meeting suggested that the following findings by visual inspection should serve as proxy indicators for the diagnosis of schistosomiasis of the lower genital tract in women from S. haematobium endemic areas: sandy patches appearing as (1) single or clustered grains or (2) sandy patches appearing as homogenous, yellow areas, or (3) rubbery papules. In this atlas we aim to provide an overview of the genital mucosal manifestations of schistosomiasis in women.Photocolposcopic images were captured from women, between 1994 and 2012 in four different study sites endemic for S. haematobium in Malawi, Zimbabwe, South Africa and Madagascar. Images and specimens were sampled from sexually active women between 15 and 49 years of age. Colposcopic images of other diseases are included for differential diagnostic purposes.This is the first atlas to present the clinical manifestations of schistosomiasis in the lower female genital tract. It will be freely available for online use, downloadable as a presentation and for print. It could be used for training purposes, further research, and in clinical practice.